A new analytical method of strain and deformation of pipeline under fault movement. (May 2019) - Zeng, Xi; Dong, Fei-fei; Xie, Xiang-dong; Du, Guo-feng
Abstract: A pipeline usually extends thousands of meters or more, and, in order to test the pipeline in the lab accurately, it is expected to develop a reasonable method to simplify the length of the model and simulate the small deformation section of the pipeline for a practical lab test. In this research, the scale model with consideration of the strengthening stage after the pipeline yielding is given to study the mechanical performance of the pipeline under fault displacement. Based on the mechanical model of the elastic foundation beam, a new analytical method of strain and deformation of pipeline is developed in which an equivalent spring model is established to simulate the small deformation section of the pipeline far away from the fault. The similarity ratio of the model is designed, and the results of the shell model with fixed boundary at both ends are compared by using ABAQUS software. On this basis, the soil-box test model with equivalent spring boundary is made. The elastic coefficients of springs at both ends are determined by N △ L curve ( N and △ L represents the interaction force and the relative displacement of pipeline-soil, respectively), and the influences of pipeline diameter, buried depth, soil and spring with different elastic coefficients on the mechanical properties of pipelines are analyzed. The results show that the two-end spring device can better control the size of the test model and enhance the reliability of the test results. The strain and deformation responses of the pipeline can be reduced by choosing larger pipeline diameter, smaller buried depth, non-cohesive backfill soil and spring with smaller elastic coefficient. Highlights: A new analytical method of strain and deformation of pipeline is developed. A N-ΔL curve including the strengthening stage after the pipeline yielding is obtained. A soil-box scale test model based on the equivalent spring boundary is accomplished. Different influencing factors on the mechanical properties of pipelines are analyzed.